The CB1R of mPFC is involved in anxiety-like behavior induced by 0.8/2.65 GHz dual-frequency electromagnetic radiation - Sun, Bin; Xue, Teng; Gao, An-ning; Wang, Xin-yu; Wu, Shuang; Liu, Xiao-man; Zhang, Li-hui; Li, Meng-hua; Zou, Dong-fang; Gao, Yan; Wang, Chang-zhen (Frontiers in Molecular Neuroscience, 2025)
As mobile phones and communication base stations become more widespread, concerns have arisen regarding the potential risks of environmental exposure to multi-frequency electromagnetic radiation (EMR) and its effects on mental health. To address these concerns, our study established a dual-frequency EMR mouse model at 0.8/2.65 GHz to explore potential molecular mechanisms and intervention targets. Our results revealed that exposure to this dual-frequency EMR significantly induced anxiety-like behavior in mice. Molecular experiments further showed a significant decrease in cannabinoid receptor type 1 (CB1R) levels in the medial prefrontal cortex (mPFC) of the mice, along with a notable reduction in the endogenous cannabinoids 2-arachidonoylglycerol and anandamide. This led to a downregulation of the entire endocannabinoid system (ECS). Additional confirmation was obtained by overexpressing and knocking down CB1R in the mPFC. We found that increasing mPFC CB1R levels could effectively reduce anxiety-like behavior, while decreasing mPFC CB1R levels exacerbated it. Furthermore, we found dual-frequency EMR induced the change of ECS in the basolateral amygdala (BLA). Notably, female mice exhibited similar behavioral phenotypes and molecular mechanisms in response to dual-frequency EMR. In summary, our study demonstrates that anxiety induced by dual-frequency EMR is closely linked to the function of the ECS in the mPFC and BLA, and that CB1R expression in the mPFC plays a significant role in modulating emotional behavior in mice.